Identifikasi Etnomatematika pada Motif Kain Tenun di Desa Weelonda - Ina, Yosefa Natalia; Lede, Yulius Keremata; Making, Samuel Rex Mulyadi; Lubur, Dorothea Novia Ludo (Indo-MathEdu Intellectuals Journal, 2025)
This study focuses on identifying ethnomathematics in woven fabric motifs in Weelonda Village, with ethnomathematics understood as the study of the adaptation of mathematics in culture and its interactions. This type of research is qualitative research using an ethnographic approach. The subjects in this study were woven fabric weavers in Weelonda Village, Southwest Sumba Regency, East Nusa Tenggara Province. The data analysis technique in this study was to systematically search for and compile data obtained from interviews, observations, and documentation. The results showed that several woven fabric motifs in Weelonda Village integrate mathematical concepts such as geometry (squares, rhombuses, triangles), making them relevant for contextual mathematics learning.